Information structure and syntactic change in Germanic and Romance languages - Bech, Kristin; Eide, Kristine Gunn (J. Benjamins, 2014)
In this article, we discuss how contrastivity can be identified in historical texts where we have no direct access to prosodic features such as stress and intonation. We depart from our knowledge of contrastivity in the modern languages and their exponence in Modern Spanish and Portuguese, where both word order and prosody play a role in expressing contrast, and compare the analysis of the modern languages to our data of Old Spanish and Old Portuguese. Our findings indicate that very little has changed with regard to the expression of contrastivity through word order. Therefore, any word order changes should be attributed to other changes in syntax and information structure, in particular changes along the given-new axis, such as the loss of preverbal information focus in Old Spanish, the loss of IP scrambling in Portuguese and the fact that, unlike today, the SV order was linked to the topicality of the subject.